Sunn Hemp (Crotalaria juncea) Seed Oil: A Potential Antioxidant for Emulgel Applications - Ditthawutthikul, Naphatsorn; Wattanasiri, Chakree; Nusontra, Nutlada; Pansanit, Acharavadee (Science Essence Journal, 2024)
Sunn hemp (Crotalaria juncea), a valuable legume, is used to improve soil quality, boost crop yields, and reduce pests. Its abundant seeds hold promise for cosmetic applications due to their content of beneficial compounds. This study investigated the antioxidant activity and fatty acid profile of sunn hemp seed oil. The oil was extracted using five different solvents: hexane, dichloromethane, ethyl acetate, acetone, and ethanol. The ethanol extract exhibited the strongest antioxidant activity, measured by its ability to scavenge free radicals (DPPH assay), with a 50% scavenging concentration (SC50) of 53.69 ± 0.02%. This ethanol extract was chosen to formulate an emulgel using a cold process technique. Different seed oil concentrations were tested. Evaluations of the prepared emulgels revealed that the one containing 1% seed oil extract displayed the most desirable properties, demonstrating good physical and chemical stability. The results suggested that sunn hemp seed oil might possess an ability to be used as an active ingredient in the emulgel formula. Further s.tudies about other formulation and clinical efficacy of formulated products should be considered.